Hydrochory in the Florida Everglades: Temporal and Spatial Variation in Seed Dispersal Phenology, Hydrology, and Restoration of Wetland Structure - Monette, Dean; Markwith, Scott H. (Ecological restoration, 2012)
Hydrochory may move species into areas appropriate for establishment, increasing the probability that species can take advantage of restored habitat. This research examined the influence of Everglades ridge and slough degradation on hydrochory; the interaction of hydrochory; hydrology, and ecosystem structure, and the role of hydrochory in ecosystem restoration. We identified 41 seed species from 2343 and 2849 seeds trapped in the intact and degraded sites, respectively. Month and the interaction of month and site type had significant effects within subjects in repeated measures ANOVA for seed density/trap, species richness, water depth, and water velocity. Percent cover of standing vegetation and periphyton, and Sørenson's Similarity Index comparing standing vegetation and the dispersing seed pool differed significantly between sites in both the wet and dry seasons. Regression analyses indicated that seed species richness and seed density/trap were significantly positively related to water depth and velocity. The timing of increasing water depths and velocity coincided with the dispersal phenology strategy in intact sloughs in late spring/early summer, which may assist the dispersal of slough species through the system into physically restored deeper water areas once they are restored. Ridge species in degraded sloughs, such as swamp sawgrass (Cladium jomaicense) and common buttonbush (Cephalanthus occidentalis), timed their seed release with peak water depths immediately before drawdown, and during substantially reduced water velocities. This strategy may increase the probability of these species being deposited on elevated peat locations.